Can South Africa use the hosting of the 2010 FIFA World Cup to address issues of unemployment and poverty? - Kunene, Merryman (My University, 2009)
Abstract: The South African government has boldly set a target for economic growth at 6 percent annually in an effort to reduce unemployment, create wealth and prosperity – effectively working towards the Millennium Development Goals (MDG) in 2015. While there are several other measures already put in place to achieve these goals, another aspect that could help the country reach its target for economic growth and development could be the successful hosting of the 2010 Fifa World Cup. The aim of this research is to interrogate ways in which the preparation and the subsequent hosting of the event could be managed in a manner that would enable the country to achieve its growth targets through infrastructure development and effective allocation of resources
Keywords: Employment; Economic growth; Poverty alleviation; Development